Assessing Mozambique's exposure to coastal climate hazards and erosion. (August 2017) - Cabral, Pedro; Augusto, Gabriela; Akande, Adeoluwa; Costa, Anjos; Amade, Nelson; Niquisse, Sérgio; Atumane, Ali; Cuna, António; Kazemi, Kiana; Mlucasse, Ramires; Santha, Rubini
Abstract: An increasing number of people in the world are living in coastal areas characterized by high geophysical and biophysical sensitivity. Thus, it is necessary to provide coastal planners with tools helping them to design efficient management plans to mitigate the negative effects caused by a growing number of coastal climate hazards that threaten life and property. We calculate an Exposure Index (EI) for the coastline of Mozambique and assess the importance of the natural habitats in reducing exposure to coastal climate hazards. We estimate, for year 2015, an increase of 276% in the number of people affected by a high, or very high, level of exposure when compared to a "Without habitats" scenario, i.e. excluding the protective effects of sand dunes, mangroves, and corals. The results of the EI are supported by the Desinventar Database, which has historic data concerning loss and damage caused by events of geological or weather related origin. These results also indicate where the most exposed areas are thereby providing useful information to design effective coastal plans that increase resilience to climate hazards and erosion in Mozambique.